Immunohistochemical, pharmacovigilance, and omics analyses reveal the involvement of ATP-sensitive K+ channel subunits in cancers: role in drug-disease interactions - Fatima Maqoud; Fatima Maqoud; Nicola Zizzo; Marcella Attimonelli; Antonella Tinelli; Giuseppe Passantino; Marina Antonacci; Girolamo Ranieri; Domenico Tricarico (Frontiers Media S.A., 2023)
Background: ATP-sensitive-K+ channels (KATP) are involved in diseases, but their role in cancer is poorly described. Pituitary macroadenoma has been observed in Cantu' syndrome (C.S.), which is associated with the gain-of-function mutations of the ABCC9 and KCNJ8 genes. We tested the role of the ABCC8/Sur1, ABCC9/Sur2A/B, KCNJ11/Kir6.2, and KCNJ8/Kir6.1 genes experimentally in a minoxidil-induced renal tumor in male rats and in the female canine breast cancer, a spontaneous animal model of disease, and in the pharmacovigilance and omics databases.Methods: We performed biopsies from renal tissues of male rats (N = 5) following a sub-chronic high dosing topical administration of minoxidil (0.777-77.7 mg/kg/day) and from breast tissues of female dogs for diagnosis (N = 23) that were analyzed by immunohistochemistry. Pharmacovigilance and omics data were extracted from EudraVigilance and omics databases, respectively.Results: An elevated immunohistochemical reactivity to Sur2A-mAb was detected in the cytosol of the Ki67+/G3 cells other than in the surface membrane in the minoxidil-induced renal tumor and the breast tumor samples. KCNJ11, KCNJ8, and ABCC9 genes are upregulated in cancers but ABCC8 is downregulated. The Kir6.2-Sur2A/B-channel opener minoxidil showed 23 case reports of breast cancer and one case of ovarian cancer in line with omics data reporting, respectively, and the negative and positive prognostic roles of the ABCC9 gene in these cancers. Sulfonylureas and glinides blocking the pancreatic Kir6.2-Sur1 subunits showed a higher risk for pancreatic cancer in line with the positive prognostic role of the ABCC8 gene but low risks for common cancers. Glibenclamide, repaglinide, and glimepiride show a lower cancer risk within the KATP channel blockers. The Kir6.2-Sur1 opener diazoxide shows no cancer reactions.Conclusion: An elevated expression of the Sur2A subunit was found in proliferating cells in two animal models of cancer. Immunohistochemistry/omics/pharmacovigilance data reveal the role of the Kir6.1/2-Sur2A/B subunits as a drug target in breast/renal cancers and in C.S.